1979
DOI: 10.1107/s0567740879008657
|View full text |Cite
|
Sign up to set email alerts
|

Structure and conformation of substituted cycloheptatrienes. I. 2,5-Dimethyl-3,4-diphenyl-1,3,5-cycloheptatriene

Abstract: C21H20 is monoclinic, space group P2~/c, with a = 11.312(5), b = 8.503 (5), c = 16.91 (1) ,4,, fl = 98.04 (1) °, Z = 4. The structure was refined to R = 0.044 for 1119 counter reflections. The sevenmembered ring is boat-shaped with structure angles a = 52.6 o and fl = 34.3 o. Empirical force-field calculations of the isolated molecule predict a = 51.0 ° and fl = 27.5 °, while a = 51.9 ° and fl = 31.9 ° were calculated considering packing effects. The enthalpy of the inversion barrier between the two boat forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The seven-membered ring has the shape of a shallow boat as shown by a small dihedral angle [35.0(6)°] between planes C1C7C6 and C2C3C4C5. Corresponding dihedral angles in cycloheptatriene derivatives are much larger [for example, 93.1° for 2,5-dimethyl-3,4-diphenyl-1,3,5-cycloheptatriene and 98.3° for 3-anilino-2-(2,4,6-cycloheptatrien-1-yl)-2-propenal] . This difference in dihedral angle values is presumably caused by significant sp character at the alkyne carbons of 3 which increases bond angles C7C1C2 [134.7(5)°] and C1C2C3 [134.4(4)°].…”
Section: Resultsmentioning
confidence: 99%
“…The seven-membered ring has the shape of a shallow boat as shown by a small dihedral angle [35.0(6)°] between planes C1C7C6 and C2C3C4C5. Corresponding dihedral angles in cycloheptatriene derivatives are much larger [for example, 93.1° for 2,5-dimethyl-3,4-diphenyl-1,3,5-cycloheptatriene and 98.3° for 3-anilino-2-(2,4,6-cycloheptatrien-1-yl)-2-propenal] . This difference in dihedral angle values is presumably caused by significant sp character at the alkyne carbons of 3 which increases bond angles C7C1C2 [134.7(5)°] and C1C2C3 [134.4(4)°].…”
Section: Resultsmentioning
confidence: 99%
“…According to an electron diffraction (ED) and a microwave (MW) investigation of CHT [4,51, the molecule is nonplanar and possesses a boat form. This has been confirmed by X-ray studies of the substituted CHTs [6][7][8][9] and AZPs [lo-121 shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 62%
“…A number of conjugated organic molecules have so far been prepared, some of which are known experimentally to assume nonplanar structures in the ground and electronically excited states. From the viewpoints of structural characteristics, chemical reactions, and physicochemical properties, a degree of pyramidalization in nonplanar conjugated molecules has attracted a good deal of attention, and the topics on measures of pyramidalization have been reviewed by several authors. As will be shown below, since the total energy of a molecule can be partitioned into the four energetic components, our interest in nonplanar conjugated molecules is to elucidate what happens inside the molecule when it is subject to the pseudo-JT distortion from planarity. In such a structural change, it will be expected that non-nearest-neighbor interactions become important, according as the molecule folds its molecular skeleton.…”
Section: Introductionmentioning
confidence: 99%